IMPLEMENTASI METODE WAHDAH PADA PROGRAM MENGHAFAL AL-QUR’AN DI SMP IT DARUL FIKRI - Naila Sari (Anfa Mediatama, 2023)
The purpose of this study was to describe the implementation of the wahdah method in memorizing the Qur'an for students at SMP IT Darul Fikri, to describe the evaluation of the implementation of the wahdah method in memorizing the Koran to students at SMP IT Darul Fikri and to describe the obstacles to implementation the wahdah method in memorizing the Koran for students at SMP IT Darul Fikri. The research method that the writer uses is qualitative research. The process and meaning or perspective of the subject in qualitative research is emphasized more, compared to quantitative research. In qualitative research, the theoretical basis is used by researchers as a guide, so that the research process is more focused and in accordance with the facts found in the field. The type of research is descriptive. Qualitative research method is a descriptive research and tends to use analysis. The results showed that the planning of the Al-Qur'an tahfizh program had been carried out quite well, the results of the planning of the tahfizh Al-Qur'an program at Darul Fikri IT Middle School included setting targets, setting goals, determining strategies for tahfizhul Qur'an, formulating and determining methods tahfizhul Qur'an and conduct planning evaluation. Nevertheless, several things need to be considered in planning the tahfizh program, namely more consideration in determining the size of the halaqah group for Darul Fikri students because an effective halaqah group consists of 5 to 7 people, and in determining the method of tahfizhul Qur'an it needs to be considered carefully. mature because the method used has an important role in the success of students memorizing the Al-Qur'an in accordance with the specified target.